Suppose that q(z) = 1, and p(z) = (1 + z)(1 + 3z).(adsbygoogle = window.adsbygoogle || []).push({});

We wish to express q(z)/p(z) in the form

where A and B are constants. To find them, we multiply through by p(z) =

(1 + z)(1 + 3z) and obtain

1 = A(1 + 3z) + B(1 + z)

= (A + B) + (3A + B)z

Im fine up to this point, But according to my notes it is obvious that A + B = 1 and (3A + B)z = 0.

I can not see why this is the case?

Any help would be greatly appreciated.

**Physics Forums | Science Articles, Homework Help, Discussion**

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Homework Help: Partial fractions with generating functions

**Physics Forums | Science Articles, Homework Help, Discussion**